Use of acoustic emission b(Ib)-values to quantify damage in composites - Jung, Doyun; Yu, Woong-Ryeol; Na, Wonjin (Elsevier, 2020)
This study reports a new damage quantification method for fiber-reinforced composites using the acoustic emission (AE) b(Ib)-value. Plain-woven carbon fiber/epoxy composite specimens were prepared and their AE signals were analyzed under cyclic loadings (10 cycles per step, up to 700 MPa of tensile stress). The analysis showed that fiber breakage and interfacial failure occurred in the low stress region, which caused complex macrocracks to form. During the test, b-values (given by the relationship between the number and amplitude of AE hits) decreased continuously, providing information on the overall extent of the damage. However, this was not obvious in the large stress region (under 700 MPa) due to significant AE hits with low amplitude from matrix cracking and complex fracture behavior, raising b-value. In contrast, a modified parameter (Ib-value) showed a continuously decreasing trend in all regions, indicating its suitability as a health monitoring parameter.